La conexión de algunos rasgos geológicos y geomorfológicos con la tectónica (1981)
The surface features of the earth are caused by two types of processes: exogenic and endogenic ones.  The exogenic processes are due to the action of wind, water and ice; their character is that they are of a random nature. The endogenic processes are caused by the action of the tectonic stress field; their character is that they are of a non-random nature. Conversely, it is possible to determine the geotectonic stress field from the phenomena that it has caused. To determine these, it is necessary to separate the non-random (systematic) aspects from the random aspects of a geological or geomorphological phenomenon. This has to be done by statistical techniques. The method is ilustrated in the case of the analysis of joints and of the analysis of river orientations. It is shown that the resulting tectonic directions agree with those postulated by plate tectonics in all parts of the world that have been analyzed to-date.